Harry's holiday - Moses, Antoinette (United Kingdom Cambridge University Press, 2011)
Harry's dad works away from home and his mother isn't well. He needs to help her a lot at home. But then, Harry sees a competition - he and his parents can go on holiday together. For free! but can he win ? and is it really a free holiday ?
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Human interest; Language Learning; Beginner/Elementary level; Reading books